Large-scale flow measurements and analysis for radial inlets of industrial centrifugal compressors based on multi-hole probe system - Han, Fenghui (2021)
Multi-hole probe (MHP), as a classical measuring instrument, continues to play an important role in the pressure and velocity measurements for industrial applications by virtue of its robust and reliable performance as well as the simple structure and low cost. But the flow directionality limitations and the low efficiency of traditional operations become obstacles to the large-scale measurements of MHPs. In this paper, an improved operating method is adopted for conventional MHPs to extend their measuring range of incidence angles, and a corresponding auto-measuring system has been developed to realize automatic calibration and measurement of MHPs for industrial large-scale flow measurements. Measurement uncertainties of the system have been experimentally analyzed, verifying a good accuracy: errors of 0.36° in pitch angle, 0.40° in yaw angle and 0.83% in velocity magnitude (95% CI). Furthermore, this auto-measuring system has been applied in the large-scale measurements on different radial inlets for industrial centrifugal compressors, which provide valuable flow information that was not previously available for industrial productions and assist with the improvement study. Analysis and applications in this paper prove that the developed system not only reduces the flow directionality limitations of conventional MHPs, but also significantly improves the experimental efficiency and the control-precision of the probe, achieves a good repeatability and ensures the reliability of the experimental data, which satisfies the requirements of large-scale measurements in industrial applications. Meanwhile, the portability of the system makes it more convenient and flexible to be applied in various industrial productions.